Development and validation of the Manipal Interstitial Lung Disease Education Booklet (MILD EduB) for individuals with interstitial lung disease - Revati Amin; Aswini Kumar Mohapatra; G. Arun Maiya; Vishak Acharya; Shivashankara Kaniyoor Nagri; Suresh Sukumar; Winniecia Dkhar; Anup Bhat; Mukesh Kumar Sinha; Marita T. Dale; Jennifer A. Alison; K. Vaishali (PLoS ONE, 2026)
In India, Interstitial Lung Disease (ILD) is a significant healthcare burden. Poor outcomes are caused by delayed diagnosis and insufficient patient education (PE). In this context, the Manipal Interstitial Lung Disease Educational Booklet (MILD EduB), a culturally relevant resource for individuals with ILD in India, was developed and validated. The booklet was developed in four stages: (1) a scoping review to identify important educational themes; (2) development of a draft booklet shared with experts for review and feedback; (3) validation of the booklet by healthcare professionals using the content validity index (CVI); and (4) face validation by individuals with ILD. The initial scale-level CVI (S-CVI/Ave) was 0.79, which improved to 1.0 following modifications, indicating good expert consensus via the healthcare professionals. Face validation by individuals with ILD (n = 10) using a 4-point Likert scale demonstrated 100% agreement for readability, relevance, and design. With a Flesch Reading Ease Scale score of 80.9, the finalised booklet is considered easy to read and accessible to individuals with ILD with a wide range of reading levels. MILD EduB fills an important gap in ILD-specific educational resources, particularly in low-resource settings. Its evidence-based content and patient-centered design aim to improve adherence and self-management.